RESOLUTION OF THE EXPERT FORUM WITH INTERNATIONAL PARTICIPATION «RUSSIAN EXPERTS AGAINST CERVICAL CARCINOMA» AS PART OF THE XX INTERNATIONAL CONGRESS OF OBSTETRICIANS AND GYNECOLOGISTS (FIGO) (11 OCTOBER 2012, ROME, ITALY) - Article Editor (Union of pediatricians of Russia, 2012)
.